1996
DOI: 10.1017/s0956536100001449
|View full text |Cite
|
Sign up to set email alerts
|

The Postclassic Occupation at Otumba

Abstract: The Aztec city-state of Otumba is the focus of a long-term project of archaeological investigation. Analysis of surface and excavated ceramics and obsidian-hydration dates for the capital—Otumba—indicate a dispersed Mazapan occupation, a scattered early Aztec (Aztec II) occupation, and an intense Late Aztec (Aztec III) and Early Colonial (Aztec III/IV) occupation. In the paper we incorporate recent radiocarbon dates to refine the local late Postclassic chronology. A cluster of hydration dates suggests the earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…My earlier correlation of ceramic complexes ran into the problem that the western Mesoamerican phases corresponding to the changes tended to have one or two radiocarbon dates apiece (Beekman 1996a), but I concluded that the changes in question appeared to pertain to the period A.D. 550-900. Later radiocarbon dates from Coyotlatelco contexts in central Mexico (Nichols and Charlton 1996;Parsons et al 1996) and from La Quemada at the opposite end of the region (Nelson 1997) support this dating. But recent work in La Higuerita in central Jalisco encountered new architecture, ceramic types, and burial patterns, and excavations there have produced radiocarbon dates beginning around A.D. 400 (López Mestas, personal communication, 2005;López Mestas and Montejano Esquivias 2003), immediately following or overlapping the recently redated sequence in that area (Beekman and Weigand 2008).…”
Section: The Late Archaic Period (5000-2000 Bc)mentioning
confidence: 75%
“…My earlier correlation of ceramic complexes ran into the problem that the western Mesoamerican phases corresponding to the changes tended to have one or two radiocarbon dates apiece (Beekman 1996a), but I concluded that the changes in question appeared to pertain to the period A.D. 550-900. Later radiocarbon dates from Coyotlatelco contexts in central Mexico (Nichols and Charlton 1996;Parsons et al 1996) and from La Quemada at the opposite end of the region (Nelson 1997) support this dating. But recent work in La Higuerita in central Jalisco encountered new architecture, ceramic types, and burial patterns, and excavations there have produced radiocarbon dates beginning around A.D. 400 (López Mestas, personal communication, 2005;López Mestas and Montejano Esquivias 2003), immediately following or overlapping the recently redated sequence in that area (Beekman and Weigand 2008).…”
Section: The Late Archaic Period (5000-2000 Bc)mentioning
confidence: 75%
“…Although there are differences of opinion concerning the duration and degree of overlap among the four, their chronological placement in Fig. 4 reflects an apparent consensus among current investigators (Cowgill 1996;Evans and Freter 1996;Nichols and Charlton 1996;Parsons et al 1996).…”
Section: Tula and The Tula Region Following The Tollan Phasementioning
confidence: 86%
“…stratigraphy, and well-described ceramics, whereas the Early Postclassic period lacks these features (see Parsons et al 1996;Nichols and Charlton 1996). Based upon similarities in ceramics and other material culture, we think it is reasonable to hypothesize that the transition from Early Postclassic to Middle Postclassic assemblages in Morelos and the Basin of Mexico occurred at roughly the same time.…”
Section: Dating the Phasesmentioning
confidence: 91%
“…Among the possibilities are: ( I ) the Late Aztec phase in the Basin of Mexico starts closer to 1300 than 1350 (this is not inconsistent with the Otumba dates; see Nichols and Charlton 1996); (2) the Atlan phase starts earlier than Late Aztec, and imports such as Aztec 111 Black-onorange do not appear at Yautepec until some time after the start of Atlan; or, perhaps some combination of these or other models is needed. Only additional chronological research will settle this question.…”
Section: Dating the Phasesmentioning
confidence: 99%